Democracy in the Age of Media: A Review - Rakul Preet Kaur (Journal of Advanced Research in Journalism & Mass Communication, 2025)
The relationship between media and democracy has evolved significantly in the digital age, where the rapid advancement of technology has transformed how information is disseminated and consumed. Traditionally, media served as a cornerstone of democratic societies, providing citizens with essential information for political engagement and accountability. However, the rise of digital platforms, particularly social media, has introduced both opportunities and challenges. While digital media has democratized access to information, it has also fostered political polarization, the spread of misinformation, and the fragmentation of public discourse. This review explores the complex dynamics of media’s role in contemporary democracy, examining how digital media influences public opinion, political participation, and trust in democratic institutions. It also highlights the importance of media literacy, the need for regulation of digital platforms, and the critical role of an informed citizenry in sustaining democratic values. Ultimately, it argues that while media plays a pivotal role in shaping democratic processes, addressing its challenges is crucial to ensure that it continues to support democratic ideals in an increasingly interconnected world.